2010
DOI: 10.1136/emj.2008.069427
|View full text |Cite
|
Sign up to set email alerts
|

Point of care troponin decreases time in the emergency department for patients with possible acute coronary syndrome: a randomised controlled trial

Abstract: POC testing for troponin in the ED tended to reduce the LOS for possible ACS patients. The degree of this benefit is likely to be markedly dependent on its acceptance and uptake by attending personnel, and on the ED setting in which it is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…A before/after study design8 using POC troponin testing for ACS demonstrated shorter ED LOS and time to admission decisions, a quasi-randomised trial9 demonstrate only a trend to shorter ED LOS, while two randomised trials failed to demonstrate a benefit 10 11. In studies of POC testing using machines that perform a variety of blood tests, two before/after studies demonstrated shorter ED LOS12 13 while a third did not,14 a small randomised trial found a shorter ED LOS,15 but a large randomised trial was unable to demonstrate a difference in ED LOS, hospital LOS, admission rates or mortality 16.…”
Section: Discussionmentioning
confidence: 99%
“…A before/after study design8 using POC troponin testing for ACS demonstrated shorter ED LOS and time to admission decisions, a quasi-randomised trial9 demonstrate only a trend to shorter ED LOS, while two randomised trials failed to demonstrate a benefit 10 11. In studies of POC testing using machines that perform a variety of blood tests, two before/after studies demonstrated shorter ED LOS12 13 while a third did not,14 a small randomised trial found a shorter ED LOS,15 but a large randomised trial was unable to demonstrate a difference in ED LOS, hospital LOS, admission rates or mortality 16.…”
Section: Discussionmentioning
confidence: 99%
“…For the diagnostic accuracy outcome effect size, one study [61] documented an adverse effect rated “Substantial”, one study [59]) had a favorable effect rated “Substantial”, one study [38] had a favorable effect rated “Moderate”, and three [43][60][62] had effect sizes rated “Minimal/None”. One study [37], rated “Fair” with “Moderate” effect size, found improvement in TAT, but there was not sufficient evidence to evaluate further.…”
Section: 0 Evidence Review Synthesis and Resultsmentioning
confidence: 99%
“…While POCT cTn has the potential to reduce TAT [59][41], and LOS [60], the body of evidence regarding this practice was insufficient and inconsistent for conclusions. However, there is sufficient published evidence to determine the equivalency of POCT assays to laboratory assays and we recommend additional studies be conducted to measure the effect of POCT cTn implementation.…”
Section: 0 Additional Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Turnaround times from blood sampling to results can therefore be highly important both to meet policy targets and for efficient patient disposition and initiation of definitive treatment [11]. Previous studies have had varying results regarding the effect of POC devices on length of stay with some showing improvement and some not [11,17,[20][21][22][23]. However, some authors ascribe the inconsistent improvement in lengths of stay, occurring in some centres but not others, to how POC results are incorporated into the assessment pathways.…”
Section: Discussionmentioning
confidence: 99%